2000
DOI: 10.1038/sj.onc.1203825
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and nuclear exclusion of the forkhead transcription factor FKHR after epidermal growth factor treatment in human breast cancer cells

Abstract: Akt, when activated by IGF/insulin, can phosphorylate forkhead transcription factors. We undertook this study to determine whether epidermal growth factor (EGF) treatment could produce a signaling cascade resulting in phosphorylation of the forkhead transcription factor FKHR in a breast cancer cell line, MDA-MB-231. After establishing ErbB1, cbl, PI3 kinase and Akt were activated in EGF treated MDA-MB-231, we determined by immunoblot with FKHR antiserum that the electrophoretic mobility of FKHR was retarded af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…FKHR could not be detected in N.1 clones and AFX did not exhibit a distinct phosphorylation pattern in the cell clones analysed (data not shown). In N.1 cells, FKHRL1 accumulated in the nucleus under serumstarved conditions, which was also shown by others in different cell systems, 21,22 and nuclear expression of FKHRL1 was further increased in Cdc25A-overexpressing cells (Figure 2a, upper panel, compare lanes 1 and 5). It was demonstrated that 14.3.3 proteins bind to phosphorylated FKHRL1 (pFKHRL1) and cause its relocation from the nucleus into the cytoplasm 23,24 where it becomes rapidly degraded.…”
Section: Cdc25a Causes Dephosphorylation and Activation Of Fkhrl1supporting
confidence: 85%
“…FKHR could not be detected in N.1 clones and AFX did not exhibit a distinct phosphorylation pattern in the cell clones analysed (data not shown). In N.1 cells, FKHRL1 accumulated in the nucleus under serumstarved conditions, which was also shown by others in different cell systems, 21,22 and nuclear expression of FKHRL1 was further increased in Cdc25A-overexpressing cells (Figure 2a, upper panel, compare lanes 1 and 5). It was demonstrated that 14.3.3 proteins bind to phosphorylated FKHRL1 (pFKHRL1) and cause its relocation from the nucleus into the cytoplasm 23,24 where it becomes rapidly degraded.…”
Section: Cdc25a Causes Dephosphorylation and Activation Of Fkhrl1supporting
confidence: 85%
“…(6, 44, or 23) was digested with EcoRI, separated in a 1% agarose gel and subjected to Southern analysis using an AKT1 probe Transgene expression under the control of the MMTV LTR is strongly induced during pregnancy (Krane and Leder, 1996). Since Akt is involved in multiple cell survival pathways that are relevant to mammary epithelium (Dufourny et al, 1997(Dufourny et al, , 2000Jackson et al, 2000;Lu et al, 1999;Zhou et al, 2000), the e ect of AKT1 overexpression in mammary epithelium during involution was examined. Female transgenic and non-transgenic littermates from founders 6 and 44, ranging in age from 16 ± 22 weeks, were bred and allowed to nurse their pups.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44] The PKB/AKT phosphorylates FKHR at 3 residues (Thr 24 , Ser 256 and Ser 319 ) by phosphoinositide 3-kinase (PI 3 K) pathway that results in the nuclear exit and inactivation of apoptosis related gene. [45][46][47] Furthermore, the expression of AKT resulted in phosphorylation of FKHR and translational upregulation of cyclin D1 levels. 48 At the same time, DYRK1A also phosphorylated FKHR, although on a different residue (Ser 329 ), and leads to the decrease of FKHR present in the nucleus.…”
Section: Discussionmentioning
confidence: 99%